2019
DOI: 10.1002/jssc.201900407
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis and characterization of multiple constituents of corn silk aqueous extract using ultra‐high‐performance liquid chromatography combined with quadrupole time‐of‐flight mass spectrometry

Abstract: Corn silk is a well‐known traditional Chinese medicine that has been widely used for its antidiabetic, antioxidant, antihyperlipidemic, and other effects in China for thousands of years. Numerous studies have revealed that corn silk contains multiple bioactive constituents that are beneficial for human health. However, the constituents of corn silk in vivo remain ambiguous. In this study, high‐throughput ultra‐high‐performance liquid chromatography combined with quadrupole time‐of‐flight mass spectrometry tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…The bioactive activity observed in this study may be related to the chemical characterization of the extract, as shown by studies by Wang et al. (2019). When extracting bioactive components from the aqueous extract of the corn stigma and identified the presence of 76 compounds, including caffeic acid and 10 of its derivatives, (E)‐p‐coumaric acid and two of its derivatives, ferulic acid and four of its derivatives, and five flavones.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The bioactive activity observed in this study may be related to the chemical characterization of the extract, as shown by studies by Wang et al. (2019). When extracting bioactive components from the aqueous extract of the corn stigma and identified the presence of 76 compounds, including caffeic acid and 10 of its derivatives, (E)‐p‐coumaric acid and two of its derivatives, ferulic acid and four of its derivatives, and five flavones.…”
Section: Resultssupporting
confidence: 70%
“…The reducing effect of the microbiological growth of CSE observed in rump steaks may be related to its phytochemical composition, according to the data obtained in this study in the in vitro analyses of CSE phytochemicals, such as phenolic compounds, flavonoids, alkaloids, and organic acids, which are known to act as strong antimicrobial agents (Arribas et al., 2019; Boeira et al., 2020; Wang et al., 2019). The active film based on gelatin and corn starch incorporated with different concentrations of CSE could, therefore, suppress microbial growth in meat and, in turn, improve its refrigeration life.…”
Section: Resultsmentioning
confidence: 55%
“…The fragment information at m / z 177.0209 was detected as aglycone without C ring. Compared to the MS spectra data and references [34,36] compound 46 was tentatively identified as naringin.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the loss of a glucuronic acid (176 Da) and hexose residue (glucose 162 Da, rhamnose 146 Da) were often seen in flavonoid glycosides. Compounds 24 , 33 , 34 , 36 , 39 , 46 , 48 , 56 , 57 , 62 , and 66 were considered as puerarin, scoparin, isorhamnetin-3- O -neohespeidoside, kaempferol-3- O -glucorhamnoside, methyl hesperidin, naringin, hesperidin, 5,8-dihydroxy-6,7-dimethoxyflavone, juglanin, naringenin, and hesperetin, respectively [31,32,33,34,36]. Take compound 46 as an example (Figure 6), it had [M − H] − ion at m / z 579.17156 in the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Information on herbal compounds can be obtained in two ways. One method is directly based on compound analysis techniques [7][8][9], and the other is based on the retrieval from database and literature [1,10,11]. Herbal medicines contain multiple compounds with different polarities.…”
Section: Introductionmentioning
confidence: 99%